LMX Differentiation and Group Outcomes: A Framework and Review Drawing on Group Diversity Insights. (January 2021) - Buengeler, Claudia; Piccolo, Ronald F.; Locklear, Lauren R.
In this review, we address inconsistencies and a lack of clarity in the study of leader-member exchange (LMX) differentiation and group outcomes. We do so by drawing on another highly visible group dispersion literature in the management domain, group diversity, based on the recognition that LMX quality is a characteristic on which group members vary. Utilizing insights from Harrison and Klein's typology of group diversity constructs, we introduce a framework that specifies the meaning and shape of three variations of differentiated leader-member relationships in groups and connects each construct with implications in terms of theorizing and measurement. Specifically, our framework conceptualizes LMX differentiation as LMX separation (dispersion in LMX relationships as disagreement or opposition regarding an opinion, perception, or position), LMX variety (dispersion in LMX relationships as distinctiveness in kind, source, or category), and LMX disparity (dispersion in LMX relationships as inequality in concentration of valued social assets or resources). We then apply this framework to conduct a systematic review of the LMX differentiation literature with particular attention to alignment among a study's descriptions of the construct, application of theory, expected group outcomes, and construct measurement. Finally, we offer recommendations for future research and for applying our framework to enhance reliability, validity, and generalizability in studies of LMX differentiation and group outcomes.